2013
DOI: 10.1118/1.4770281
|View full text |Cite
|
Sign up to set email alerts
|

A review of breast tomosynthesis. Part II. Image reconstruction, processing and analysis, and advanced applications

Abstract: Many important post-acquisition aspects of breast tomosynthesis imaging can impact its clinical performance. Chief among them is the reconstruction algorithm that generates the representation of the three-dimensional breast volume from the acquired projections. But even after reconstruction, additional processes, such as artifact reduction algorithms, computer aided detection and diagnosis, among others, can also impact the performance of breast tomosynthesis in the clinical realm. In this two part paper, a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(115 citation statements)
references
References 179 publications
(166 reference statements)
2
107
0
3
Order By: Relevance
“…Two major differences among the modalities were that cancers missed by 2D alone tended to be of size 11-20 mm or to have a mass as the major radiological sign, compared with the other two modalities; and cancers missed by 2D + DBT were less likely to be of grade 2 or to have density less than 50% than the other two modalities. (29) 26 (29) 27 (27) 164 (24) 2 67 (56) 43 (48) 57 (56) 373 (55) 3 18 (15) 21 (23) 17 (17) 140 (21) Breast density < 50% 80 (66) 69 (73) 70 (66) 488 (70) ≥ 50% 42 (34) 26 (27) 36 (34) 195 (30) Dominant radiological feature Mass 68 (55) 45 (47) 52 (49) 479 (69) Microcalcification 12 (10) 12 (13) 16 (15) 88 (12) Distortion/ASD 42 (34) 37 (39) 37 (35) 126 (18) None 1 (1) 1 (1) 1 (1) 4 (1) Receiver operating characteristic analysis…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two major differences among the modalities were that cancers missed by 2D alone tended to be of size 11-20 mm or to have a mass as the major radiological sign, compared with the other two modalities; and cancers missed by 2D + DBT were less likely to be of grade 2 or to have density less than 50% than the other two modalities. (29) 26 (29) 27 (27) 164 (24) 2 67 (56) 43 (48) 57 (56) 373 (55) 3 18 (15) 21 (23) 17 (17) 140 (21) Breast density < 50% 80 (66) 69 (73) 70 (66) 488 (70) ≥ 50% 42 (34) 26 (27) 36 (34) 195 (30) Dominant radiological feature Mass 68 (55) 45 (47) 52 (49) 479 (69) Microcalcification 12 (10) 12 (13) 16 (15) 88 (12) Distortion/ASD 42 (34) 37 (39) 37 (35) 126 (18) None 1 (1) 1 (1) 1 (1) 4 (1) Receiver operating characteristic analysis…”
Section: Resultsmentioning
confidence: 99%
“…71 A number of publications have summarised and reviewed both the technical and the clinical aspects of DBT and have speculated on its potential application in breast imaging. 23,[25][26][27]61,63,64,72,73 The AETNA policy report, 74 a combined recommendation from the American College of Radiologists, the American Cancer Society and the American College of Obstetrics and Gynaecologists, considers that breast tomosynthesis imaging is experimental and investigational because of insufficient evidence of its effectiveness. An Australian health technology review acknowledged that DBT systems were likely to replace 2D in screening when existing 2D equipment is due for replacement 75 and an overview of the evidence and issues to be considered in relation DBT and breast cancer screening raised concerns regarding additional radiation exposure and the learning curve for radiologists to accurately interpret DBT results.…”
Section: Reader Performancementioning
confidence: 99%
“…In DBT, multiple low dose projections of the breast are acquired over a limited angular range; these projections are then used to calculate a pseudo-3D reconstruction of the imaged tissue. [2][3][4][5][6] Preliminary studies have shown that DBT has the potential to improve the clinical performance of breast cancer screening and/or diagnosis. [7][8][9][10][11][12] Current DBT systems, including the Selenia Dimensions (Hologic Inc., Bedford, MA) used in this study, lack x-ray scatter reduction measures, be it in software or hardware.…”
Section: Introductionmentioning
confidence: 99%
“…3-D breast imaging modalities that mitigate tissue superimposition effects include magnetic resonance imaging, digital breast tomosynthesis, and more recently, dedicated breast computed tomography (bCT) and 3-D automated breast ultrasound. [1][2][3][4]5,6 Studies involving these latter two emerging technologies are promising, but more research is needed to determine their potential role in breast cancer screening and/or diagnosis. [7][8][9][10][11][12] The use of 3-D imaging modalities, however, requires viewing 3-D image volumes on two-dimensional displays and increases the amount of data that radiologists need to interpret.…”
mentioning
confidence: 99%